A Glance at the methods for detection of apoptosis qualitatively and quantitatively [Apoptozun nitel ve nicel olarak tespitine yönelik metotlara kısa bir bakış] - (:unkn) unknown (Turkish Biochemistry Society, 2011)
While programmed cell death, apoptosis, occurs as a necessary and natural event for multicellular organisms, necrosis is a form of unplanned cell death as a result of pathological or chemical trauma. There are numerous molecular and morphological differences between these two forms of cell death, whose decision is based on the type and dose of the stress. As apoptosis is critical for homeostasis of an organism, i.e. for development to adult stage, disease progression, or response to different stimuli, it is being studied more extensively in the area of basic research and clinics, and the need for quick detection of apoptosis and well established criteria for the discrimination of apoptosis have also gained more popularity. Here, we review our knowledge on the most commonly used methods for both qualitatively and quantitatively measuring apoptosis, including morphological imaging (i.e. through light, fluorescence, phase contrast or electron microscopy), immunohistochemical (i.e. Annexin V-FITC, TUNEL, M30 antigen or caspase 3 detection), biochemical (i.e. DNA- or protein-based electrophoresis or flow cytometry-based methods), immunological (i.e. ELISA), and molecular biology techniques (i.e. array-based techniques) while focusing on the differences for distinction between the two forms of cell death. Indeed, one has to confirm that cell death occurs through apoptosis based on more than one of these protocols depending on the specific purpose of the user. © TurkJBiochem.com.
Keywords: Annexin V-FITC; Caspase-3; Cytochrome c; DNA fragmentation; Hematoxylin/Giemsa Staining; M30 Antigen; Propidium Iodide/Hoechst Staining; TUNEL